Variabilité climatique au Tchad : Perception et stratégie d’adaptation paysanne à Kélo (Tchad) - Abdoulay Mfewou; Julius Tata Nfor; Paul Nadji (VertigO, 2022)
In southern Chad, the analysis of climate variability, from 1983 to 2012, shows that the annual rainfall totals are 606.9 mm and the average annual temperature is 28.9°C; with sequences of recurrent floods and droughts. This situation has a considerable impact on the territories, which are experiencing strong rapid changes, plunging rural populations into misery and chronic food insecurity. Addressing the issue of climate risk management for peasant society, political decision-makers intervene weakly to support local adaptation mechanisms. Through the empirical perception, the peasants adopt the strategy of reforestation in the lowlands by including a peasant a reforested young tree named Balanites aegyptiaca which is a small thorny tree, which can be a hundred years old and which can survive two years without rain. This study was conducted in Kélo (59,560 inhabitants) in southern Chad. It analyzes farmers' perceptions and adaptation strategies in the face of climate variability. The data relating to the know-how of the farmers were collected, for five (5) months, through a questionnaire from 140 heads of households chosen at random in this area. Our results show that the farmers (80%) have significant empirical knowledge of the agricultural calendar and knowledge of the varieties of trees adapted to the Sahel such as Balanites aegyptiaca, Faidherbia albida, Acacia raddiana, the date palm... which resists better to climatic variability, the request of the public authorities is to multiply the plants in the nursery and redistribute them to the farmers for reforestation in the area to fight against the advance of the desert. Farmers also showed that resilience stems from empirical knowledge through consultation with elders. They perceive a drop in rainfall (75%), an increase in temperatures (95%) and strong winds (96.7%). As a result, a strong adaptation of the cropping system by transplanting sorghum and rice. Use of local varieties (maize, millet, sorghum, rice) with a short cycle and low agricultural yield. The construction of water reservoirs to carry out manual and regular watering if necessary. Politicians and researchers must strongly intervene to guide and supervise farmers in supporting peasant strategies for resilience to climatic hazards.